Analysis Soil and Water Conservation Strategies In Ciwidey Sub-Watershed using SWAT Model - Rizkina, Tasya; Yanidar, Ramadhani; Astuti, Ariani Dwi (Jurnal Serambi Engineering, 2026)
The Ciwidey sub-watershed serves as a buffer zone to meet the raw water needs of Bandung Regency. This study aims to assess the hydrological impacts of soil and water conservation techniques and evaluate the combined effects under extreme rainfall on runoff and baseflow dynamics. The Soil and Water Assessment Tool (SWAT) hydrological model was employed to predict flow discharge in the Ciwidey sub-watershed. The methodology included collecting hydrological, climate, and land-use data, delineating watersheds, forming Hydrological Response Units (HRUs), and conducting model calibration, validation, and simulation of a surface runoff. The spatial pattern of the Bandung Regency Regional Spatial Plan (RTRW) for 2016–2036 resulted model simulations predicted a surface runoff of 1,084.36 mm/year under extreme rainfall. The watershed conservation program demonstrates strong implementation of agroforestry and reforestation throughout the watershed region, with 42,313 hectares currently under management with 21 individual conservation projects in 9 districts. The conservation planning program consists of implementation Agroforestry (52.6%), reforestation (39.6%) and 7,8% infiltration well, with Pasir Jambu District and Subbasin 6 emerging as focus area of comprehensive conservation. The study demonstrates that integrating soil and water conservation is crucial for sustainable water resource management and flood risk reduction in rapidly developing regions.